2013
DOI: 10.1002/jnr.23248
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex N-methyl-D-aspartate receptor/nitric oxide/cyclic guanosine monophosphate pathway modulates both tachycardic and bradycardic baroreflex responses

Abstract: Neural reflex mechanisms, such as the baroreflex, are involved in regulating cardiovascular system activity. Previous results showed that the ventral portion of the medial prefrontal cortex (vMPFC) is involved in modulation only of the cardiac baroreflex bradycardic component. Moreover, vMPFC N-methyl-D-aspartate (NMDA) receptors modulate the bradycardia baroreflex, but the baroreflex tachycardic component has not been investigated. Furthermore, glutamatergic neurotransmission into the vMPFC is involved in act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 55 publications
(91 reference statements)
1
7
0
Order By: Relevance
“…Stimulation of hippocampus may evoke BP and HR decrement, responses that are abolished by the inhibition of the MPFC (Ruit & Neafsey, ). The MPFC sends projections to brainstem areas related to cardiovascular tonic control (Fisk & Wyss, ; Vertes, ), and we demonstrated that MPFC modulates baroreflex function (Ferreira‐Junior et al, , ). Therefore, MPFC may be a relay area for hippocampal control in the baroreflex function once hippocampus has no direct projections to the brainstem (Cenquizca & Swanson, ).…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Stimulation of hippocampus may evoke BP and HR decrement, responses that are abolished by the inhibition of the MPFC (Ruit & Neafsey, ). The MPFC sends projections to brainstem areas related to cardiovascular tonic control (Fisk & Wyss, ; Vertes, ), and we demonstrated that MPFC modulates baroreflex function (Ferreira‐Junior et al, , ). Therefore, MPFC may be a relay area for hippocampal control in the baroreflex function once hippocampus has no direct projections to the brainstem (Cenquizca & Swanson, ).…”
Section: Discussionsupporting
confidence: 51%
“…The peripheral information about BP status is integrated into the solitary tract nucleus that projects to other brainstem areas as rostral and caudal ventrolateral medulla and vagal nuclei (Guyenet, ). However, supramedullary areas such as amygdala (Fortaleza, Ferreira‐Junior, Lagatta, Resstel, & Correa, ), medial prefrontal cortex (MPFC; Ferreira‐Junior, Fedoce, Alves, Correa, & Resstel, ; Ferreira‐Junior, Fedoce, Alves, & Resstel, ) and hippocampus (Ferreira‐Junior et al, , ) can modulate the baroreflex activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the MPFC modulates baroreflex function (Ferreira‐Junior et al . , ). Therefore, the MPFC may be a part of the neural circuitry that allows the VH to modulate cardiac baroreflex function.…”
Section: Discussionmentioning
confidence: 99%
“…Both acute DA and glutamate effects in rat brain, and the alteration of long-term potentiation via glutamatergic tone and metabotropic glutamate receptors are crucial to acute responses to psychostimulant drugs and addiction (Zhang, Loonam et al 2001), (Kalivas 2009). The ventral medial prefrontal cortex, with abundant glutamatergic transmission, is involved in modulating bradycardic/tachycardic reflexes (Ferreira-Junior, Fedoce et al 2013). Cardiac vagal preganglionic neurons are also responsible for heart rate modulation, and receive glutamatergic signaling input (Hildreth and Goodchild 2010).…”
Section: Discussionmentioning
confidence: 99%